The moderating effect of communication climate on the relationship between negotiation issues and subjective utility perception - Torunoğlu, Dilek (My University, 2004)
Bu araştırmada müzakerelerin nesnel sonuçları ile öznel fayda algısı arasındaki ilişkide iletişim ikliminin rolü incelenmiştir. Çatışan çıkar veya fikirlere sahip, ancak çatışma durumunun çözümü için birbirlerine bağımlı olan tarafların karar vermek amacıyla iletişim kurmaları sürecine müzakere denir. Müzakerenin sonunda ortaya çıkan nesnel sonuç (gündem konularına ilişkin) hakkında taraflar farklı derecelerde fayda algısına sahip olmaktadırlar. Buna öznel fayda algısı denmektedir. Öznel fayda algısının maddi ve manevi olmak üzere iki alt faktörü ile müzakerenin nesnel sonucu arasındaki ilişkiye bakıldığında, müzakerenin nesnel sonucunun öznel fayda algısı genelinde doğrudan bir etkisi olduğu ve alt faktörlerden de sadece maddi fayda algısını değiştirdiği gözlemlenmiştir. Yani nesnel sonuç beklenilenin üzerinde olduğunda, maddi fayda algısı artmakta, nesnel sonuç beklenilenin altında olduğunda ise maddi fayda algısı düşmektedir. Araştırmanın bağımlı değişkeni olan öznel fayda algısı sadece müzakerenin nesnel sonucundan etkilenmemektedir. Müzakerenin psikolojik faktörleri de denebilecek olan manevi unsurları öznel fayda algısını etkilemektedir. Bu araştırma çerçevesinde, manevi unsurlardan biri ve şartlı değişken olarak iletişim iklimi ele alınmış ve müzakerelerin nesnel sonuçları (araştırmanın bağımsız değişkeni) ile öznel fayda algısı arasındaki ilişkide iletişim ikliminin rolü incelenmiştir. İletişim ikliminin öznel fayda algısı üzerinde hem doğrudan etkisi olduğu saptanmış, hem de müzakere sonuçları ile öznel fayda algısı arasındaki ilişkinin yön ve derecesini değiştirdiği bulunmuştur. Buna göre savunmacı olan iletişim iklimlerinde öznel fayda algısı azalırken, yapıcı iletişim iklimi olan müzakerelerde öznel fayda algısı artmaktadır. Araştırmada ayrıca cinsiyetin öznel fayda algısını etkileyip etkilemediği de incelenmiş, cinsiyet faktörünün şartlı değişken olarak müzakerenin nesnel sonuçlarına ilişkin öznel fayda algısı üzerinde manidar bir fark yaratmadığı görülmüştür. Bununla birlikte, cinsiyet şartlı değişkeninin iletişim iklimi ile etkileşime girerek, öznel fayda algısı üzerinde ortak bir etki yarattığı gözlemlenmiştir;müzakerenin nesnel sonucundan bağımsız olarak, iletişim ikliminin yapıcı olduğu durumlarda kadınlar erkeklere göre daha yüksek öznel fayda algısına sahipken, iletişim ikliminin savunmacı olduğu durumlarda da kadınların öznel fayda algıları erkeklere göre daha düşük olmaktadır. The moderating effect of communication climate on the relationship between negotiation issues and subjective utility perception has been examined in this study. Negotiation is a communication process where the negotiating parties, who have conflicting interests or opinions, depend on each other to make a decision with the purpose of resolving the mentioned conflicts. The parties have differing degrees of utility perception regarding the outcomes (related to the items of the agenda) of the negotiation. This is called subjective utility. When the relationship between negotiation outcome and subjective utility's two sub-factors tangible and intangible is examined, it has been found that there is a main effect of negotiation outcome on the subjective utility perception, and that negotiation outcome has changed the utility perception for tangibles. Thus when the negotiation outcome is above the expected, the utility perception for tangibles increases, and when the negotiation outcome is below the expected, the utility perception for the tangibles decreases. Subjective utility perception, which is the dependent variable of this study, is not affected only by the outcome of the negotiation. The intangibles, which may be assumed as the psychological factors of a negotiation, also affect the subjective utility perception. Within the frame of this research, communication climate, as the moderating variable and as one of the intangibles, has been examined and the role of communication climate on the relationship between negotiation outcomes (issues) (independent variable) and the subjective utility perception has been investigated. It is found that communication climate has a main effect on subjective utility perception and a moderating (interaction) effect on the relationship between negotiation outcomes and subjective utility perception so as to change the degree and direction of the relationship. Thus, subjective utility perception decreases when the communication climate is defensive, whereas the subjective utility perception increases when communication climate is supportive in negotiations. Additionally, gender effect in negotiations is also examined. Accordingly it is found that gender as a moderating variable does not have a moderating effect on the relationship between negotiation outcomes and subjective utility perception. Yet gender variable has an interaction effect with communication climate, on the subjective utility perception. So independent from the negotiation outcome, when the communication climate is supportive, women have higher degree of subjective utility perception compared to men, and when the communication climate is defensive, women have lower degree of subjective utility perception, compared to men.
Keywords: Örgütsel Davranış